2017
DOI: 10.3390/rs9111129
|View full text |Cite
|
Sign up to set email alerts
|

Deriving 3-D Time-Series Ground Deformations Induced by Underground Fluid Flows with InSAR: Case Study of Sebei Gas Fields, China

Abstract: Multi-temporal Interferometric Synthetic Aperture Radar (MT-InSAR) technique has proven to be a powerful tool for the monitoring of time-series ground deformations along the line-of-sight (LOS) direction. However, the one-dimensional (1-D) measurements cannot provide comprehensive information for interpreting the related geo-hazards. Recently, a novel method has been proposed to map the three-dimensional (3-D) deformation associated with underground fluid flows based on single-track InSAR LOS measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…According to Even et al [20], 2D and 3D displacements in vertical, east-west and north-south directions derived from InSAR LOS measurements holds a fundamental role for the integrated analysis and integration with other data of oil and gas reservoirs. A number of successful InSAR studies applied 3D and 2D decompositions and cosine corrections techniques to derive vertical and horizontal deformations for oil and gas fields [1,21,22]. The present research specifically focused on the comparative aspects of LOS measurements with the consequently derived vertical and horizontal deformations from 3D and 2D decompositions and cosine corrections in the Tengiz oilfield for the period of 2018-2020.…”
Section: Introductionmentioning
confidence: 99%
“…According to Even et al [20], 2D and 3D displacements in vertical, east-west and north-south directions derived from InSAR LOS measurements holds a fundamental role for the integrated analysis and integration with other data of oil and gas reservoirs. A number of successful InSAR studies applied 3D and 2D decompositions and cosine corrections techniques to derive vertical and horizontal deformations for oil and gas fields [1,21,22]. The present research specifically focused on the comparative aspects of LOS measurements with the consequently derived vertical and horizontal deformations from 3D and 2D decompositions and cosine corrections in the Tengiz oilfield for the period of 2018-2020.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that, following the deformation time series retrieval operation, the S-1 IWS P-SBAS processing chain automatically supplies various value-added information on the ongoing deformation phenomena. Indeed, in addition to the estimate of the mean deformation velocity, it also automatically identifies possible deformation signals characterized by a periodic behavior with respect to time, such as those relevant to oil and gas extraction/storage activities and water withdrawal, which represent significant DInSAR applications in the energy source storage [53] and hydrogeological [54] fields. This is done by computing the correlation coefficient of each pixel's detrended time series with a sinusoid with a one-year period.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that surface motions occur in three spatial dimensions (east, north and up) (Fuhrmann and Garthwaite, 2019). Many studies successfully used both descending and ascending tracks to assess actual vertical and horizontal displacements (Fialko 2006;Klemm et al, 2010;Chang et al, 2017;Liu et al, 2017;Motagh et al, 2017;Fernandez et al, 2018;Aslan et al, 2019a;Aslan 2019b;Alatza et al, 2020;Ho Tong Minh et al, 2020;Pawluszek-Filipiak and Borkowski, 2020;Staniewicz et al, 2020). As it was mentioned before, the use of the cosine correction approach for the Tengiz oilfield was only decided based on the studies by Bayramov et al, 2021 which had shown non-significant differences of vertical displacements derived from the 3D and 2D decompositions and cosine corrections.…”
Section: Discussionmentioning
confidence: 99%